Integration Journey: The Social Mobility Trajectory of Ethnic Minority Groups in Britain - Yaojun Li (Social Inclusion, 2018)
This article studies the processes of social mobility by the main ethno-generational groups in Britain. We compare the origin-education-destination (OED) links between the first- and second- generation ethnic minority groups with those of whites, with a particular focus on whether the second generation are getting closer to whites than do the first generation in the links, hence becoming increasingly integrated into the socio-economic lives of British society. Using data from the UK Household Longitudinal Study and adopting structural equation modelling (SEM) methods, we find strong evidence of first-generation setback, and some signs of second-generation catch-up. Indians and Chinese are making progress, but the two black groups and Pakistanis/Bangladeshis are lagging behind. The analysis shows persisting ethnic disadvantages in the labour market in spite of their high levels of educational achievement, and it also shows an emerging order of ethnic hierarchy, running from Indian, Chinese, black Caribbean, Pakistani/Bangladeshi to black African groups.